Model programmes of support for families raising 'difficult' orphan children - Oslon V.N (Moscow State University of Psychology and Education, 2017)
The paper describes a system of organizational and technological measures that shape the principles, conditions, procedure, forms and methods of supporting families raising so-called 'difficult' orphan children, i.e. disabled children, adolescents, siblings. These children have specific needs when it comes to living in a family; their integration into the family takes much longer and is usually more complicated as compared to other orphans. It is not uncommon for families to be afraid of such children and to refuse taking care of them. Still, the key factor of successful family integration of these children is a special system of support. Model programmes that were developed in 2016 at the request of the Ministry of Education and Science of the Russian Federation can well be considered as methodological and procedural guidelines for the emerging system of support for families taking care of orphans with special family needs as well as for specialist training courses.